The determinants of employees’ well-being: a case of support business and procurement department at Menara Telekom Malaysia, Kuala Lumpur / Nur Hanisah Abdul Mutalib - Abdul Mutalib, Nur Hanisah (Faculty of Business and Management, 2019)
In Malaysia, there is a notable increase in the percentage of stress among employees. This study shows the relationship between employees’ well-being and leader support, flexible work hour and job involvement. The purpose of this research is to study the determinants of employees’ well-being in Support Business and procurement department at Menara Telekom Malaysia. The research mainly focuses on few major factors of employees; well-being, which is leader support, flexible work hour and job involvement. This paper does not include all the possible factors towards employees’ well-being; rather it is only focus on few selected factors. Results provided for this study shows two hypotheses are significant such as leader support and job involvement. Meanwhile for flexible working hour is not significant. Therefore, there are relationships between leader support and job involvement with employees’ well-being. But there is no relationship between flexible working hour and employees’ well-being in Menara Telekom Malaysia.